Perceived Parental Autonomy Support, Psychological Control, and Grit among High Schoolers in Pakistan - Zulfiqar, Najia; Akram, Hifza (International Journal about Parents in Education, 2025)
Parent-adolescent relationships facilitate or debilitate the development of interests and perseverance to achieve long-term goals. This question is addressed by examining the role of perceived maternal and paternal autonomy support and psychological control in grit development among high schoolers. Two factors of grit i.e., perseverance of effort and consistency of interest are separately measured. Participants were 300 high school students in grades 9-12, aged 15-19 years. Data were collected on self-report measures of the Perceived Parental Autonomy Scale and Grit-Original Scale. Findings show that perseverance of effort and consistency of interest have a positive relationship with parental autonomy support and a negative relationship with psychological control. Autonomy support was a positive predictor while psychological control was a negative predictor of grit. Adolescents had a homogenous perception of maternal and paternal behaviors. The findings offer practical guidelines to parents to adopt autonomy-support behaviors for grit development among adolescents.